Kebebasan Pers Ditinjau dari Kode Etik Jurnalistik: Analisis Isi Pemberitaan Politik Pada Media Cetak Radar Sorong - Aziz, Nurul Asriani Muh.; Fatimah, Fatimah; Ahriani, Andi (Al-Hikmah: Jurnal Dakwah dan Komunikasi, 2021)
The research aims to determine the implementation of Radar print media on press freedom in the journalistic code of ethics, knowing the content of political news in text analysis, and find out the violations of the journalistic code of ethics in political reporting in the Radar Sorong print media. This type of research is qualitative by using the text analysis approach of Robert Entman's model. Data is collected through literature studies or texts from news content, field observations, and interviews. The results showed that the implementation of Radar Sorong's print media on press freedom in the journalistic code of ethics was maximal. Meanwhile, based on Robert Entman's framing model analysis, print media journalists are still framing news that only involves one party. Through the framing analysis, the researcher quickly concludes that the violation of the journalistic code of ethics that journalists are still carrying out from the print media Radar Sorong is Article 1, namely "Indonesian journalists must act independently, produce news that is accurate, balanced, and does not have bad intentions." Thus, the freedom of the press in the Radar Sorong print media has not been fully accounted for and is still separated from the control of the journalistic code of ethics.